Penglibatan lbu Bapa Di Pra Sekolah - Ishak, Salma (Penerbit Universiti Sains Malaysia, 1987)
TABIKA or Taman Bimbingan Kanak-kanak Is a pre-school educational programme organised by KEMAS or Community Development Section of the Ministry of National and Rural Development. The set up of the kindergarten encouraged participation from parents. Nonetheless, parental involvement in the activities of this pre-school programme has not been encouraging.